Comparing the effect of two kinds of organic fertilizer: manure and vermicompost on the sorptivity and saturated hydraulic conductivity of the soil (Damascus University Journal of agriculture sciences, 2026)
Soil sorptivity and the saturated hydraulic conductivity are the most important hydrodynamic properties of the soil. These properties aren't affected only by the amount of organic fertilizer applied, but also by the organic fertilizer type. The aim of this recent research was to compare the effects of two kinds of organic fertilizers: Manure and vermicompost on the soil sorptivity (S) and saturated hydraulic conductivity (Ks). The measurements of S and Ks were carried out using two sets of soil containing different amount of both types of organic fertilizer. Both soils sets were prepared from the same initial soil. Each set comprises 5 soil samples containing 2, 5, 10, 15, and 20 % of organic fertilizer.To measure the soil sorptivity, the Philip equation for the vertical infiltration was used. Whereas, the saturated hydraulic conductivity of the soil was measured by using constant head method.The results of this study showed that the two types of organic fertilizer influence the soil sorptivity and saturated hydraulic conductivity differently. The soil sorptivity increased with increasing the amount of both types of organic fertilizer added to the soil. However, the soil sorptivity was higher in the soils manure-added compared to soils treated with vermicompost. The results showed also that the manure may increase more the drainage pores number of the soil compared to the vermicompost. However, the vermicompost seems to be more able to retain water than manure.
Keywords: Manure; vermicompost; Soil sorptivity; saturated hydraulic conductivity